Immersive learning of the young generation using a mobile learning lab - Eduard N. Ayubov; Svetlana V. Neveleva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In order to counter modern threats, knowledge and ablity to act in the face of emerging dangers are necessary. It is not possible to solve these problems without proper training of the population, including the younger generation, in the field of life safety. The development of the modern education system involves the introduction of modern technologies and innovative educational projects into the educational process, including immersive teaching methods. Immersive learning is the most effective and safe way to develop sustainable skills for safe behavior in various emergency and dangerous situations. The aim of this study is to increase the level of training of the younger generation in the field of life safety. To achieve the aim set, the authors: analyzed the main normative legal acts regulating the issues of training the population in the field of life safety; studied previously completed scientific papers and publications in this field of research; the problematic issues of training the younger generation in the field of life safety are considered; identified the most effective ways of training the younger generation based on the use of modern technologies. To solve the identified problems and achieve the research aim, the authors propose using the latest achievements and trends in the educational environment to develop a unique educational product – the mobile educational laboratory «Country of Safety». The paper substantiates the relevance and effectiveness of the creation and use of a mobile training laboratory in the education system, analyzes the experience of using similar complexes on the topic of road safety in Moscow and the Moscow region. The main emphasis is put on the organization of practical training of the younger generation on the basis of a mobile educational laboratory using game forms of learning, virtual reality technologies and environment modeling using 3D visualization. As conclusions, the planned results of the development and implementation of the mobile training laboratory «Country of Safety» in the activities of both the Ministry of Emergency Situations of Russia and educational organizations are proposed.